THE CIRCADIAN CLOCK AND HUMAN ATHLETIC PERFORMANCE - Vitošević, Biljana (Bulletin of Natural Sciences Research, 2017)
The importance of circadian clock in managing of key muscle physiological processes, and therefore the impact on athletic performance is well studied. Specifically chronobiology examines the mechanisms of the biological clock and the consequences of disrupting its rhythm. Although a body of literature indicates that the peak performance of notable indicators of athletic performance exerts mainly in the afternoon and evening hours which is attributed to increased temperature of the body, certain variables such as vigilance, alertness and cognitive domains can influence the shift of the peak performance during the day. In addition, athletes face issues of desynchronization of their circadian rhythm during frequent transcontinental travels, since their performance is reduced and the adjustment of the biological clock requires some recommendations in the training process and behavioral approach. This review focuses on some current studies on endogenous and exogenous factors which affect the circadian rhythm in order to achieve better sport results, evaluation of the impact chronotype through chronometric tests and revising more valuable  determinants of sport performance, as well as the application of new mathematical models in individual treatment of recovery of athletes in the phase of resynchronization.
Keywords: circadian disruption; athletic performance; chronobiology; circadian clock